Meningkatkan Kemampuan Membaca Permulaan Menggunakan Metode Cantol Roudhoh Pada Anak Tunagrahita Ringan di SLB Negeri Tidore - Mariyani Hi. Tamrin (Jurnal Ilmiah Wahana Pendidikan, 2020)
This study aims to determine the increase in pre-reading skills in children with mild mental retardation in SLB Negeri Tidore in the use of the Cantol method. The research method used in this research is a quantitative approach with the Classroom Action Research (CAR) type model. Class action research is research that is oriented towards the application of action with the aim of improving the quality or solving problems in a group of subjects under study and observing the level of success or the consequences of their actions, to then be given follow-up actions that are perfection of actions or adjustments to conditions and situations so that the results are obtained. Better The results showed an increase in the ability to read early on in children with mild mental retardation. The conclusion that can be drawn in this study is that the use of flakat board media can improve the early reading ability of mild mentally retarded children in SLB Negeri Tidore.